The Sublime in Philip K. Dick's Flow My Tears, the Policeman Said. Issue 5 (19th October 2020) - Behrooz, Niloufar; Jannessari Ladani, Zahra; Pirnajmuddin, Hossein
ABSTRACT: Associated with feelings of woe and wonder in the face of something that is too complex to comprehend, the sublime is still a highly relevant concept in contemporary fiction. Philip K. Dick's speculative novels are filled with high-tech entities and futuristic worlds, as manifestations of posthumanist discourses, that instill a sense of bewilderment in the readers. Dick's "fictional" domains and characters progressively challenge our very definition of humanity and reality providing us with an updated transformed version of the sublime we will refer to as the posthuman sublime. The novels are saturated with baffling worlds within worlds that are home to beings who can no longer be easily categorized as either human or non-human. Dickian posthuman entities, then, are located not so much in a borderless dimension but on the very borders themselves. An encounter with such indeterminacies that defy human understanding leads to an overwhelming feeling of awe, wonder, and even parodic confusion, characteristic of the kind of sublime we find in Dick's world. This article attempts to explore the modality of the posthuman sublime in one of Dick's well-known, yet under-researched, novels Flow My Tears, the Policeman Said in the light of theories of the sublime and posthumanism.